The Attitudes of EFL Undergraduate Students in Yogyakarta toward Academic Reading - Mia Dreina Antira Pujiningtyas; Ouda Teda Ena (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2022)
Academic reading is important for EFL undergraduate students to be successful in their studies, therefore, the student’s attitudes toward it are also crucial. Attitudes could indicate students’ tendency to be engaged in an academic reading activity or not. There are two research questions in this study which are “What are EFL students’ attitudes toward academic reading?” and “Why do the EFL students have such attitudes toward academic reading?”. A close-ended questionnaire with five points Likert scale was employed in this study. There were 30 EFL undergraduate students participating in this study. An interview was conducted with six representatives of the participants to obtain more detailed information. The study showed that the student’s attitude towards academic reading was neutral. There was no strong dislike towards academic reading and the students also had no strong feeling about the enjoyment of academic reading (2.34 ≤ x̄ ≤3.66). Factors affecting the students’ academic reading attitudes were the importance, the difficulty level, and the topic of the text, as well as the result obtained from reading the academic text.